Edward J. Hughes. Proust, Class, & Nation. Oxford, New York: Oxford UP, 2011. xiii + 287 pp. - Adeline Soldin (Studies in 20th & 21st Century Literature, 2015)
Review of Edward J. Hughes. Proust, Class, & Nation. Oxford, New York: Oxford UP, 2011. xiii + 287 pp.
Keywords: Marcel Proust; A la recherche du temps perdu; In Search of Lost Time; social class; nation